Upaya Penanganan Kerusakan Integritas Jaringan Pada Pasien Post Orif Fraktur Radius Ulna Hari Ke 0 Di Rsop. Dr. Soeharso Surakarta - Sriyanto, Sriyanto, Enita Dewi,S.Kep.,Ns.,MN (2016)
Tissue integrity is a condition in which individuals were damaged integrumen, mucous membranes, corneal, wrapping tissue or subcutaneous tissue. This resulted in a fracture and bleeding into the surrounding soft tissues around the bone. If there is a hematoma, the veins will undergo dilation resulting in the accumulation of fluid and loss of leukocytes that result in displacement, causing implamasi or inflammation that causes swelling and eventually pain.The author describes and discusses the handling of network integrity and provide nursing care in clients with tissue damage. The research method using descriptive method with a descriptive case study approach, is to perform nursing care ranging from assessment, diagnosis, intervention, implementation and evaluation of nursing. The act of nursing 3x24 hours in patients with postoperative impaired tissue integrity nursing actions performed are wound care and administration of diit TKTP. With the handling of network disruption through nursing actions such as wound care is done every 2 days, giving diit TKTP and antibiotics cefazolin patient's problem is not resolved.